Special Collection Integrated System - Wan Fauzi, Wan Noor Sazidah; Wan Ishak, Wan Izzatul Fahrah; Azman, Nur Azini; Abd Halid, Nur Lian; Sulaiman, Zuhaslinda; Mohamed Nadzri, Nur Fatin Nadia; Zakaria, Mohd Azrry; Mohd Hata, Muhammad Asyraf (2017)
Menyelesaikan masalah data penggunaan bahan koleksi khas tidak tepat